FLAIR-Wise Machine-Learning Classification and Lateralization of MRI-Negative 18F-FDG PET-Positive Temporal Lobe Epilepsy - Beheshti, Iman; Sone, Daichi; Maikusa, Norihide; Kimura, Yukio; Shigemoto, Yoko; Sato, Noriko; Matsuda, Hiroshi (Frontiers in Neurology, 2020)
Abstract: Objective: In this study, we investigated the ability of fluid-attenuated inversion recovery (FLAIR) data coupled with machine-leaning algorithms to differentiate normal and epileptic brains and identify the focus lateralization in temporal lobe epilepsy (TLE) patients with visually negative MRI. Materials and Methods: The MRI data were were acquired on a 3-T MR system (Philips Medical Systems). After pre-proceeding stage, the FLAIR signal intensities were extracted from specific regions of interest, such as the amygdala, cerebral white matter, inferior temporal gyrus, middle temporal gyrus, parahippocampal gyrus, superior temporal gyrus, and temporal pole, and fed into a classification framework followed by a support vector machine as classifier. The proposed lateralization framework was assessed in a group of MRI-negative unilateral TLE patients (N= 42; 19 left TLE and 23 right TLE) and 34 healthy controls (HCs) based on a leave-one-out cross-validation strategy. Results: Using the FLAIR data, we obtained a 75% accuracy for discriminating the three groups, as well as 87.71%, 83.01%, and 76.19% accuracies for HC/right TLE, HC/left TLE, and left TLE/right TLE tasks, respectively. Interpretation: The experimental results show that FLAIR data can potentially be considered an informative biomarker for improving the presurgical diagnostic confidence in patients with MRI-negative TLE.